Conversations with Chester - Mallari, Eulan Andrei C.
Conversations With Chester is a narrative short film about healing through self-perseverance. It follows Chester, an average worker going home from his graveyard shift, having conversations with the community cat, also named Chester. He packs his things to move out the following day. But as he keeps procrastinating, he reminisces on the last conversations he had with his ex-boyfriend Drew, who he shared the apartment with, and how their relationship was bound to never last as they wanted different things in life.